Optimization of the Automated Sales System as an Effort to Minimize Fraud & Improve Internal Control at The Distribution Company PT Sehat Selalu Banyak Rejeki - Sari, Fanda Layla; Ekasari, Kurnia; Haris, Zainal Abdul (International Journal of Business, Management and Economics, 2022)
Information systems are essential in developing a business, especially in integrating data between one role and another. In addition, the development of information systems can be utilized by management in carrying out internal controls to manage the organization or company and minimize the risk of fraud resulting in material losses. This study aims to explain how the form of efforts to optimize the sales system in a company so that it becomes an automated system as an effort to minimize the risk of fraud and forms of internal control efforts. The research method used is an agile method (to develop a web-based information system) and descriptive qualitative (to identify how to implement a strategy to minimize fraud and as an effort to carry out internal control). The results of this study provide information that the implementation of an integrated web-based system which in this study is referred to as ISSS, can assist companies in improving internal control through the efficiency and effectiveness of business processes which are also visualized in the BPMN notation. This study also explains that implementing a web-based information system presented in the ISSS makes it easier for companies to minimize fraud to reduce material losses.